Characterization of the interactome profiling of Mycoplasma fermentans DnaK in cancer cells reveals interference with key cellular pathways - Curreli, Sabrina; Benedetti, Francesca; Yuan, Weirong; Munawwar, Arshi; Cocchi, Fiorenza; Gallo, Robert C.; Sherman, Nicholas E.; Zella, Davide (Frontiers in Microbiology, 2022)
Chaperone proteins are redundant in nature and, to achieve their function, they bind a large repertoire of client proteins. DnaK is a bacterial chaperone protein that recognizes misfolded and aggregated proteins and drives their folding and intracellular trafficking. Some Mycoplasmas are associated with cancers, and we demonstrated that infection with a strain of Mycoplasma fermentans isolated in our lab promoted lymphoma in a mouse model. Its DnaK is expressed intracellularly in infected cells, it interacts with key proteins to hamper essential pathways related to DNA repair and p53 functions and uninfected cells can take-up extracellular DnaK. We profile here for the first time the eukaryotic proteins interacting with DnaK transiently expressed in five cancer cell lines. A total of 520 eukaryotic proteins were isolated by immunoprecipitation and identified by Liquid Chromatography Mass Spectrometry (LC-MS) analysis. Among the cellular DnaK-binding partners, 49 were shared between the five analyzed cell lines, corroborating the specificity of the interaction of DnaK with these proteins. Enrichment analysis revealed multiple RNA biological processes, DNA repair, chromatin remodeling, DNA conformational changes, protein-DNA complex subunit organization, telomere organization and cell cycle as the most significant ontology terms. This is the first study to show that a bacterial chaperone protein interacts with key eukaryotic components thus suggesting DnaK could become a perturbing hub for the functions of important cellular pathways. Given the close interactions between bacteria and host cells in the local microenvironment, these results provide a foundation for future mechanistic studies on how bacteria interfere with essential cellular processes.